Short grain 5 controls grain length in rice by regulating cell expansion. (October 2022) - Hu, Binhua; Chen, Weilan; Wan, Li; Li, Ting; Wang, Hao; Wang, Yangkai; Pu, Zhigang; Tu, Bin; Yuan, Hua; Wang, Yuping; Ma, Bingtian; Qin, Peng; et al.
Abstract: Grain shape is a crucial determinant of grain weight and quality and plays a vital role in rice breeding. Although many grain shape-related genes have been reported, the regulatory relationship between them has not been well characterized in rice. In this study, we report the isolation of a short-grain-length mutant called sg5 from the heavy-panicle-type hybrid rice elite restorer line 'ShuhuiR498′ (R498) after ethyl methanesulfonate (EMS) treatment. MutMap cloning revealed that SG5 encodes a Myb-like transcription factor. A missense mutation in the first exon of SG5 was found to cause an amino acid change from leucine to proline at position 197 in the mutant SG5 protein. Gene knockout and genetic complementation experiments confirmed that the point mutation in SG5 was responsible for the sg5 mutant phenotype. SG5 is mainly expressed in young panicles and hulls. In addition, the SG5 protein is found in the nucleus and does not affect subcellular localization. Histochemical observation and gene expression analysis indicated that SG5 regulates spikelet hull development by mediating cell expansion. Moreover, the expression levels of BG1, GS2, and DEP1 were reduced in sg5 plants, and dual-luciferase (LUC) assays showed that SG5 can bind to the BG1 gene promoter. The effect of pyramiding sg5 and GS3 suggests that sg5 and GS3 regulate grain length independently. The results of our study show that the missense mutation in sg5 is essential for the molecular function of SG5 and SG5 is involved in regulating cell expansion and expression of grain-shape-related genes to regulate grain length. This work provides new data to help study and understand the molecular function of SG5. Highlights: A point mutation of SG5 causes short-grain length in rice. SG5 affects the expression of BG1 ， GS2 and DEP1 in rice young panicles. SG5 and GS3 regulate grain length in independent pathways.